2011
DOI: 10.1186/1465-9921-12-27
|View full text |Cite
|
Sign up to set email alerts
|

Detrimental effects of albuterol on airway responsiveness requires airway inflammation and is independent of β-receptor affinity in murine models of asthma

Abstract: BackgroundInhaled short acting β2-agonists (SABA), e.g. albuterol, are used for quick reversal of bronchoconstriction in asthmatics. While SABA are not recommended for maintenance therapy, it is not uncommon to find patients who frequently use SABA over a long period of time and there is a suspicion that long term exposure to SABA could be detrimental to lung function. To test this hypothesis we studied the effect of long-term inhaled albuterol stereoisomers on immediate allergic response (IAR) and airway hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 50 publications
4
21
0
Order By: Relevance
“…Because their model of transfer impedance in conscious mice involved applying pressure oscillations around the body generating flow through the nose, it was unavoidable that any restriction of air flow in the nose would affect the measurement of respiratory mechanics (16). Indeed, when Zosky et al (54) used the same input impedance technique as we used in our present study they failed to find any OVA-induced bronchoconstriction, similar to what we found with OVA in a previous study (27). While it is possible that inhaled OVA triggered mast cell degranulation in the study by Hessel et al, it is, due to technical limitations of their study, impossible to resolve if the increase in respiratory resistance emanated from the nose or the lung.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Because their model of transfer impedance in conscious mice involved applying pressure oscillations around the body generating flow through the nose, it was unavoidable that any restriction of air flow in the nose would affect the measurement of respiratory mechanics (16). Indeed, when Zosky et al (54) used the same input impedance technique as we used in our present study they failed to find any OVA-induced bronchoconstriction, similar to what we found with OVA in a previous study (27). While it is possible that inhaled OVA triggered mast cell degranulation in the study by Hessel et al, it is, due to technical limitations of their study, impossible to resolve if the increase in respiratory resistance emanated from the nose or the lung.…”
Section: Discussionsupporting
confidence: 73%
“…In a recent study we attempted to induce bronchoconstriction using an OVA model in mice. This was not successful in that inhaled OVA failed to induce any significant bronchoconstriction (27). In retrospect we did stain histological cuts from five OVA-sensitized mice for mast cells but found no expansion of mast cells (data not shown).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In comparison to these animals, whereas addition of the SABA albuterol had no effect on A. Genotype matched wild type and β 2 -AR-and ßarr2-deficient mice were challenged with salmeterol or DLPC alone i.n. and assessed for airway niger-induced airway hyperresponsiveness, confirming a prior study of mice sensitized against ovalbumin [44], mice challenged with the LABA salmeterol and A. niger developed significantly greater airway hyperresponsiveness (Fig 1b). Given the relatively long duration of the challenge protocol, we considered the possibility that salmeterol was downregulating expression of the ß 2 -AR, a process termed tachyphylaxis [45], thereby potentially suppressing the ability of endogenous adrenaline to limit expression of airway hyperresponsiveness.…”
Section: Structurally Related Labas Induce Exaggerated Allergic Airwasupporting
confidence: 84%
“…R N in the large airways of OVA/OVA-treated Arg1-deficient mice was not different from that in similarly treated animals without the deletion, but H and G were markedly lower in the Arg-KO Tie2 mice. H and G primarily reflect peripheral lung function (1) and may, in allergic asthma, reflect "closure" of peripheral airways by mucous bridges (30,31,55). In agreement, the mRNA abundance of Clca3 (Gob5), which regulates mucus production, and the mucin Muc5ac were lower in OVA/OVAtreated Arg1-KO Tie2 than Arg1-Con mice.…”
Section: Discussionmentioning
confidence: 79%